A Guide to the Study and Use of Military History - Army Education Press (GHQ, Rawalpindi Army Education Press, 1982)
This Guide to the Study and Use of Military History is designed to foster an appreciation of the value of military history and explain its uses and the resources available for its study. It is not a work to be read and lightly tossed aside, but one the career soldier should read again or use as a reference at those times during his career when necessity or leisure turns him to the contemplation of the military past.
Keywords: United States -- Historiography -- Military History